2001
DOI: 10.2165/00002018-200124030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Patterns of NSAID Spontaneous Adverse Event Reports

Abstract: The temporal patterns of adverse event reports are more complex than those described in Weber's classic report. The number of reports does not reliably rise and then fall after launch and the reporting rate does not reliably decrease with time from launch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 2 publications
2
33
1
Order By: Relevance
“…Another study by Hartnell and Wilson (25) investigating the Weber effect in the United States with respect to nonsteroidal antiinflammatory drugs showed that it occurred with all five drugs included in their report, with peak incidences of adverse events occurring in the 2nd year after each drug was introduced. A study by Wallenstein and Fife (15) showed that three of five nonsteroidal antiinflammatory drugs they studied followed a temporal pattern consistent with the Weber effect, whereas two of five did not. The influence of the Weber effect suggests that the increase in adverse events associated with gadobenate dimeglumine in our study could be attributed to epidemiologic reporting bias and may not reflect a true difference in adverse events based on the pharmacologic structure of the contrast medium.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study by Hartnell and Wilson (25) investigating the Weber effect in the United States with respect to nonsteroidal antiinflammatory drugs showed that it occurred with all five drugs included in their report, with peak incidences of adverse events occurring in the 2nd year after each drug was introduced. A study by Wallenstein and Fife (15) showed that three of five nonsteroidal antiinflammatory drugs they studied followed a temporal pattern consistent with the Weber effect, whereas two of five did not. The influence of the Weber effect suggests that the increase in adverse events associated with gadobenate dimeglumine in our study could be attributed to epidemiologic reporting bias and may not reflect a true difference in adverse events based on the pharmacologic structure of the contrast medium.…”
Section: Discussionmentioning
confidence: 95%
“…These dates were chosen to reflect a period 2 years before and 3.5 years after a change in prime vendor contract at our institution that resulted in the substitution of gadobenate dimeglumine for gadopentetate dimeglumine. A 3.5-year period (instead of a 2-year period) after this switch was chosen to account for the Weber effect, which can be responsible for transient elevations in the rates of adverse events after introduction of a new drug or changes in use of an existing drug (13)(14)(15) and which tends to peak in the 2nd year.…”
Section: Participantsmentioning
confidence: 99%
“…It is widely accepted that when a drug first receives marketing authorization, there is generally a substantial increase in the spontaneous reporting of ADRs (especially during the first two years on the market), which then plateaus and eventually declines. This epidemiological phenomenon is called "Weber effect" and was repeatedly shown for non-steroideal antinflammatory drugs [63][64][65]. This aspect may be related to the increased attention of clinicians towards a novel drug and may intuitively imply that the number of new signals detected reaches a peak over time with a subsequent decline.…”
Section: Dmas: Caveatsmentioning
confidence: 90%
“…However, the diagnosis of AML may be assumed to be generally reliable because ITP patients are diagnosed and treated by specialists in hematology who are assumed to be specialists in AML compared to general practitioners. Finally, our analysis is affected by various limitations of spontaneous reports conducted in postmarketing settings, such as underreporting, the effects of publicity and media attention and the temporal relationship between drug launch and the rate of reporting (19)(20)(21)(22). Moreover, detailed information, such as the type of AML based on the FAB classification, is not included in the FAERS.…”
Section: Discussionmentioning
confidence: 99%